Homocysteine Levels Are not Related to Telomere Length in Cord Blood Leukocytes of Newborns - Sinkey, Rachel G.; Salihu, Hamisu M.; King, Lindsey M.; Paothong, Arnut; Louis-Jacques, Adetola; Pradhan, Anupam; Bruder, Karen L.; Zoorob, Roger; Siegel, Erin; Riggs, Bridget; Whiteman, Valerie E. (American Journal of Perinatology, 2016)
Objective Elevated homocysteine (HC) levels and/or shortened telomere length (TL) are associated with adverse medical conditions. Our objective is to investigate the relationship between HC and TL in cord blood leukocytes of newborns.Study Design This is a nested study from a prospective cohort from 2011 to 2012 in pregnant women admitted for delivery at a university-affiliated hospital. Cord blood was collected at delivery and genomic DNA was analyzed using quantitative PCR. The telomere-to-single copy gene ratio method was employed to quantify TL. Newborn HC levels were measured. generalized linear regression modeling (GLM) and bootstrap statistical analyses were performed.Results Seventy-seven maternal-fetal dyads with a mean gestational age of 39 weeks were included. The distribution of the coefficient of homocysteine showed most values greater than zero demonstrating that homocysteine had a positive relationship with TL. In 915 of 10,000 (9.15%) iterations, the p-value was < 0.05 demonstrating a positive effect.Conclusion Increasing newborn concentrations of HC are not associated with decreasing TL. Larger, prospective studies are needed to confirm these findings and long-term implications.
Keywords: bootstrapping statistical methodology; fetal telomere length; homocysteine; umbilical cord blood